Respuesta :

Answer:

Point Form:

( − 46 /3 , − 44 /3 )

Equation Form:

x = − 46 /3 ,  y = − 44 /3

Step-by-step explanation:

Combine  1 /2 and  x .

y = x /2 − 7

2 x − y = − 16

Replace all occurrences of  y  in  2 x − y = − 16  with  x /2 − 7 .

y = x /2 − 7

2 x − ( x /2 − 7 ) = − 16

 Simplify  

2 x − ( x /2 − 7 ) .

y = x /2 − 7

3 x /2 + 7 = − 16

Solve for  

x

in the second equation.

y = x /2 - 7

x = − 46 /3

Replace all occurrences of  x  in  y = x /2 − 7 with  − 46 /3 .

y = − 46 /3 /2 − 7

x = − 46 /3

Simplify  − 46 /3 /2 − 7 .

y = − 44 /3

x = − 46 /3

The solution to the system of equations can be represented as a point.

( − 46 /3 , − 44 /3 )

The result can be shown in multiple forms.

Point Form:

( − 46 /3 , − 44 /3 )

Equation Form:

x = − 46 /3 ,  y = − 44 /3